Millennium Development Goal 5: Afghanistan in Focus - Ghosh, Pratiti (KnE Life Sciences, 2018)
An estimated maternal mortality ratio (MMR) of 1,600-2,200 was reported in 4 Afghan provinces in 2002. Badkshan province recorded highest MMR of 6500. Millennium Development Goal 5 (MDG 5) aimed to improve maternal health between 1990-2015 by (a) reducing MMR by three quarters from the baseline and (b) achieving universal access to reproductive health. In Afghanistan, MDGs were adopted in 2005 with a deadline of 2020. All six indicators used to monitor and evaluate MDG 5 showed positive change. Three of them were on target: MMR, number of births attended by skilled birth attendants (SBA), and antenatal coverage. MMR target of 400 by 2015 was reached by 2010. SBA attended birth increased by 41%. Antenatal coverage rose by 48%. The other 3 indicators are slower to change. Afghanistan adopted several strategies to reach MDG5: (i) training to increase the number of midwives, community nurses and doctors, (ii) availability of comprehensive care at all levels of healthcare facilities and (iii) better data collection methods. This first-of-its-kind review involving Afghanistan explores maternal mortality in the context of MDG 5, the past and present conditions of maternal health, factors that impacts MMR and concludes with suggesting future directions.